Keragaman Karakter Varietas Lokal Padi Pasang Surut Kalimantan Selatan - Wahdah, Raihani; Langai, Bambang F.; Sitaresmi, Trias (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
Artificial mutation could be used in the formation of base population for selection. Local varieties which have a wide distance of relationship are expected to have a greater opportunity for obtaining more diverse offspring. The purpose of this study was to select five distinct local tidal swamp rice varieties of South Kalimantan that could be used for parental mutation. The study was conducted from March to December 2009. The distance of varietal relationship was estimated by cluster analysis using the SPSS Programme Version 11.5. Selection of the five best varieties was carried out by the Exponential Rank Method (ERM) applying 7 criteria, namely plant height, number of panicles, panicle length, grain weight/panicle, number of grains/panicle, weight of 1000 grains, and grain yield. Results of the cluster analysis based on a 82.5% similarity level showed that diversities of the 40 accessions of local tidal swamp rice in South Kalimantan were spread in four clusters, namely Cluster I (13 varieties), Cluster II (1 varieties), Cluster III (6 varieties) , and Cluster IV (20 varieties). Five varieties that were selected based on the cluster analysis and the ERM were Siam Harli, Siam Unus (Bumi Makmur), Siam Kuatek, Datu, dan Siam Unus (Barambai).